Mechanical and optical properties of a borosilicate glass used to improve the finishing of 3Y-TZP restorations - Silva, Ana Carolina da [UNESP]; Rodrigues, Camila da Silva [UNESP]; Silva, Juliana de Freitas Gouveia [UNESP]; Sabino, Clarice Ferreira [UNESP]; Thim, Gilmar Patrocínio; Marinho, Renata Marques de Melo [UNESP]; Campos, Tiago Moreira Bastos (FapUNIFESP (SciELO), 2024)
Borosilicate glass was developed to enhance the mechanical behavior and smoothness of dental zirconia as an alternative to conventional glaze. This study assessed the mechanical and optical properties of 3 mol% yttria-stabilized tetragonal zirconia polycrystal (3Y-TZP) coated with borosilicate glass or a commercial glaze fired for an extended period of time. Disc-shaped 3Y-TZP zirconia specimens (Zpex, Tosoh) were sintered at 1550°C for 2 hours. The specimens were divided into three groups: as-sintered (control, C); commercial glaze (G); and borosilicate glass (SL). The glaze and borosilicate glass were applied over the zirconia and fired for 20 minutes at 950°C and 1200°C, respectively. Biaxial flexural strength, fractography, X-ray diffraction (XRD), roughness (Ra and Rz), fracture toughness (Vickers indentation method), color difference (∆E00), and translucency (TP00) analyses were conducted. The t-test or the one-way ANOVA and Tukey’s tests were used to analyze the data (α = 0.05). Flexural strength data were subjected to the Weibull analysis. The SL group exhibited the highest flexural strength (1025.8 MPa), whereas the C (859.41 MPa) and G (816.0 MPa) groups exhibited similar values. The SL group also had the highest characteristic strength. The fracture origin in all groups was on the zirconia surface. XRD analysis revealed that the specimens from the SL group contained tetragonal, cubic, and monoclinic phases. The SL group presented the lowest surface roughness. Fracture toughness in the SL group was lower than in the C group, but similar to that observed in the G group. The translucency and color differences observed in the G and SL groups were similar. Borosilicate glass enhanced the flexural strength of 3Y-TZP, promoted the smoothest surface, and exhibited optical properties similar to those of the glaze.
Keywords: Boron; Ceramics; Glass; Mechanical Test